«Linguae Vasconum Primitiae»-ren peritestualitateaz eta euskararen gramatizazioaren primiziaz - Arcocha-Scarcia, Aurelia (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2008)
This article focuses on the epitextual and material elements of Linguae Vasconum Primitiae (Bordeaux 1545). By means of a new methodological reading of the first book printed in Basque, the paper aims to make the book «speak». On the basis of Genette's definition of epitext, it analyses the elements on the title-page, the dedicatory epistle in prose, the «Advertant» or warning about linguistic rules, the final sentence or colophon, the typographic Roman characters and the punctuation. Furthermore, the coat of arms on the contemporary leather cover indicates that the book might have been kept for some time in the library of Louis I of Bourbon, prince of Condé, who was Jeanne d'Albret's brother-in-law and the Calvinists' military leader. Therefore, the epitextual and material analysis confirms that LVP was printed in the mid-16th-century atmosphere of the humanists of Bordeaux and Aquitaine, and it is more than likely that educated Basques, in order to achieve that goal, might have begun to think about the grammatisation of the Basque language before 1545. LVP's author Bernard Echepare dedicated the book to Bernard Lehet (Lahet), lawyer of the parliament of Bordeaux and great lover of music and poetry, although it is not known to what extent Lehet was involved in the printing process of the book. In order to have a better grasp of the circumstances in which LVP was born, it can be said that of the different kinds of poetic texts in the book (love poems, autobiographic accounts, metalinguistic texts) it is the religious ones that better demonstrate Echepare's ideological position. According to these, the author would have been close to the Erasmian attitude of the beginning of the 16th century, and the religious poetry discourse of LVP would be the first printed «Christian Doctrine» written in Basque language. LVP has been recently digitalised by the «Bibliothèque nationale de France» and can be read online at the following address: http://gallica.bnf.fr/ark:/12148/btv1b8609513p.r=Linguae+Vasconum.langEN